On an inequality of smoothing - Paulauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. И. Паулаускас. О неравенстве сглаживанияV. Paulauskas. Apie suglodinimo nelygybę